DECISION ANALYSIS OF EFFECTIVE HOSPITAL FUNDING MECHANISMS IN JKN (JAMINAN KESEHATAN NASIONAL) ERA - Purna, Ade
The main problem for the fifth year in a row of JKN Progrm Implemntation is the balance sheet of the Social Security Fund (Dana Jaminan Sosial/DJS) managed by BPJS Kesehatan has never been balanced. In 2018 the DJS balance sheet have deficit that reach 11.3 Trillion Rupiah, an increase from the previous years. BPJS Kesehatan prioritizes an effective, efficient and fair financing system for health care partners. In this research, to define the problems and the criteria that related to the hospital funding mechanism is using internal (Annual Internal Audit) and eksternal assesment (ServQual survey). The criteria that affect the financing system for health services in the hospital namely: 1) Utilization Effectiveness; 2)Ease of Administration; 3)Fraud Prevention; 4) Communication Effectiveness; 5)Standarization of Health Care Provider. The AHP with pairwise comparison model is used to determine and appraise the criteria tha most affect the effectiveness of alternatives for Hospital Funding Mechanism in JKN era. The SMART method is used to calculated and choose best alternatives of three system of hospital funding mechanism, that are INACBgs, Global Budget, and Fee For Service The total sum of the value of each criterion multiplied with the weight of each criterion that refers to the value of weight that calculated previously using AHP Method and the best result is INACBGs. As the recomendation of this research, there must be a mix system financing concept between INACBGs-Global Budget so that the all effectiveness parameters of the hospital financing system can be met.